Pengaruh literasi keuangan dan perilaku keuangan terhadap keputusan investasi - Kurniawan, Reza; Wahidah, Winda Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze financial literacy, financial behavior, and investment decisions and determine the effect of financial literacy and financial behavior on investment decisions in active students of the Faculty of Economics, Nurtanio University, Bandung, class of 2018–2019. The sample collection technique uses purposive sampling. The number of respondents in this study was 140. This type of research uses a quantitative approach that is descriptive and associative. The tool used in this research is a multiple linear regression test. The results showed that financial literacy, financial behavior, and investment decisions of active students at the Faculty of Economics, University of Nurtanio Bandung, had a good category, and financial literacy had a positive and significant effect on investment decisions. Financial behavior had a positive and significant effect on investment decisions, as well as financial literacy and financial behavior having a positive and significant effect on investment decisions. This means that the better the financial literacy and financial behavior, the better the investment decisions will be.